Ответы и объяснения

  • Участник Знаний
2014-01-18T18:12:29+00:00
1) x^2 - 6x + 5 = 0
D= 36 - 20 = 16
x1 = (6+4)/2 = 5
x2 = (6-4)/2 = 1

2) x^2 - 5x = 0
x(x-5) = 0
x = 0
x = 5

3) 6x^2 + x - 2 = 0
D= 1 + 8*6 = 49 = 7^2
x1 = ( - 1 + 7)/ 12 = 6/ 12 = 1/2
x2 = ( - 1 - 7)/12 = - 8/12 = - 4/6

4) 3x^2  - 48 = 0  /:3
x^2 - 16 = 0
x^2 = 16
x = ± 4

5)
x^2 + 18x + 65 = 0
D = 324 - 260 = 64 = 8^2
x1 = ( - 18 + 8)/ 2 = - 10/2 = - 5
x2 = ( - 18 - 8)/2 = - 13

6)
0,6x + 2x^2 = 0
x( 0,6 + 2x) = 0
x = 0
x = - 0,3